2010
DOI: 10.1017/s001677460000069x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoecological study of a Weichselian wetland site in the Netherlands suggests a link with Dansgaard-Oeschger climate oscillation

Abstract: CopyrightOther than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open content license (like Creative Commons).Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…At the latitude of our study site (40 S), the La Niña (El Niño) phase of ENSO is associated with wet (dry) conditions in summer (Montecinos and Aceituno, 2003). This event might have triggered frequent sediment flux into the Lake Vizcacha, explaining the presence of Glomus, a spore associated with eroded soils (van Geel et al, 1995). This interpretation is also supported by the low values of organic content between 8100e2300 cal yr BP (Fig.…”
Section: Middle Holocene (8100e4200 Cal Yr Bp)supporting
confidence: 57%
“…At the latitude of our study site (40 S), the La Niña (El Niño) phase of ENSO is associated with wet (dry) conditions in summer (Montecinos and Aceituno, 2003). This event might have triggered frequent sediment flux into the Lake Vizcacha, explaining the presence of Glomus, a spore associated with eroded soils (van Geel et al, 1995). This interpretation is also supported by the low values of organic content between 8100e2300 cal yr BP (Fig.…”
Section: Middle Holocene (8100e4200 Cal Yr Bp)supporting
confidence: 57%
“…The ages from Oerel were obtained by the enrichment method applied at that time (Grootes, 1977). Van Geel et al (2010) found a clearly expressed warming event dated between 46.6 and 54.6 ka calBP (by a combination of OSL and radiocarbon dating, the latter around the limit of the method) in a peat deposit from the central Netherlands and, based on those datings, correlated it with DeO event 12 or 14. Vaquero et al (2013) in their Spanish rock shelter (see above) identified also a warm interval between 46 and 52 ka BP that they correlated with DeO oscillations 14 to 17.…”
Section: Previous Recognition Of Mid-weichselian Interstadial Records and Their Correlation Hypotheses With Ocean And Ice Records: A Selementioning
confidence: 92%
“…Here consistent dates between 40 and 60,000 years were obtained, the youngest one by 14 C, and the older ones by OSL dating (Van Geel et al, 2010). Here consistent dates between 40 and 60,000 years were obtained, the youngest one by 14 C, and the older ones by OSL dating (Van Geel et al, 2010).…”
Section: Final Remarksmentioning
confidence: 54%
“…An example is the dating of selected seeds from another borderline (in terms of 14 C age) sequence from Wageningen. Here consistent dates between 40 and 60,000 years were obtained, the youngest one by 14 C, and the older ones by OSL dating (Van Geel et al, 2010). More intercomparisons between 14 C and OSL dating of such sequences are underway (Van der Plicht & Wallinga, in preparation).…”
Section: Final Remarksmentioning
confidence: 58%